2012
DOI: 10.1093/ajae/aar138
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Farm Commodity and Retail Food Policies on Obesity and Economic Welfare in the United States

Abstract: gave us substantial assistance with some calculations, and two anonymous reviewers and participants at several workshops and conferences provided helpful comments and suggestions. We gratefully acknowledge these helpful contributions to this work. The views expressed here are those of the authors and not necessarily those of the U.S. Department of Agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 31 publications
1
61
0
Order By: Relevance
“…Of these three studies, two were ex ante modelling studies, one from the Netherlands,11 one from the USA,12 13 and one was an ex post evaluation using econometric and regression analysis of a policy in Egypt 14. These three studies evaluated different policy scenarios in diverse settings with a range of health outcomes (table 2 Panel B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these three studies, two were ex ante modelling studies, one from the Netherlands,11 one from the USA,12 13 and one was an ex post evaluation using econometric and regression analysis of a policy in Egypt 14. These three studies evaluated different policy scenarios in diverse settings with a range of health outcomes (table 2 Panel B).…”
Section: Resultsmentioning
confidence: 99%
“…The potential impacts of the removal of established farm subsidies (ie, output price policies) were modelled in two studies, one in the Netherlands11 and one in the USA,12 13 and the impact of a long-running public distribution system policy in Egypt was evaluated in the final study 14. Two studies reported change in body weight as their health outcome,12–14 and one study estimated change in disability-adjusted life-years (DALYs) and life expectancy 11…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miao, Beghin and Jensen (2010) reported similar findings for taxing the sugar content of foods. Okrent and Alston (2012) developed a model of the U.S. farm and food industry expressly designed for analyzing such questions. Key findings from this work are in keeping with economic intuition.…”
Section: Food Taxes and Subsidiesmentioning
confidence: 99%
“…Such policies generally are found to have small effects on food consumption, obesity and overall nutrition and health; to be regressive; and to enhance government revenue but sometimes with large social welfare costs (e.g., Kuchler, Tegene, and Harris 2004;Chouinard et al 2007). However, Okrent and Alston (2012) found that taxes on calories would be comparatively efficient as a means of reducing obesity, and would yield significant net social benefits. Some have proposed changes to food and nutrition programs, to limit the use of food stamps (SNAP benefits) to certain types of 'healthy' foods, but economic arguments suggest that such changes may introduce more problems than they would solve ).…”
Section: Introductionmentioning
confidence: 99%